Locomotor behaviour of Blattella germanica modified by DEET - Sfara, Valeria (2013)
N,N-diethyl-3-methylbenzamide (DEET) is the active principle of most insect repellents used worldwide. However, its toxicity on insects has not been widely studied. The aim of this work is to study the effects of DEET on the locomotor activity of Blattella germanica . DEET has a dose-dependent repellent activity on B. germanica. Locomotor activity was significantly lower when insects were pre-exposed to 700 μg/cm2 of DEET for 20 or 30 minutes, but it did not change when pre-exposure was shorter. Locomotor activity of insects that were pre-exposed to 2.000 μg/cm2 of DEET for 10 minutes was significantly lower than the movement registered in controls. No differences were observed when insects were pre-exposed to lower concentrations of DEET. A 30-minute pre-exposure to 700 μg/cm2 of DEET caused a significant decrease in locomotor activity. Movement was totally recovered 24 h later. The locomotor activity measured during the exposure to different concentrations of DEET remained unchanged. Insects with decreased locomotor activity were repelled to the same extent than control insects by the same concentration of DEET. We demonstrated that the repellency and modification of locomotor activity elicited by DEET are non-associated phenomena. We also suggested that the reduction in locomotor activity indicates toxicity of DEET, probably to insect nervous system.